THE DEFINITION OF THE LEGISLATIVE PROCESS IN THE RUSSIAN FEDERATION - Екатерина Александровна Пискунова (Sovremennye Issledovaniâ Socialʹnyh Problem, 2014)
This article was prepared within the framework of thesis «A Legislative process in the regions of Russian Federation». There are numerous approaches to the concept of the legislative process in the Russian Federation. There is no legal definition of the legislative process. The lack of a single term that describes the activities of the legislative process, leads to uncertainty in theory and practice of Constitutional law. The article deals with the analysis of the definition of the legislative process in the Russian Federation. The article provides various scientific views on the question about the nature of legislative process, highlighted the theoretical and practical problems of this kind of constitutional process. Ultimately the author gives his own concept of the legislative process in the Russian Federation. DOI: http://dx.doi.org/10.12731/2218-7405-2013-9-64